The Influence of Teams Games Tournament (TGT) toward Students’ Interest in Arabic Language Learning - Fauzi, Moh. Fery; Buhun, Miftahul Fadliah; Purwadi, Agus (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2019)
This study aimed to determine the effect of cooperative learning model of TGT type in the interest of learning Arabic language in VII grade students at MTs. Negeri Banggai Kepulauan, Central Sulawesi. The approach used in this study was a quantitative using a correlational research design. The data collecting technique was observation and questionnaires. Data was analyzed using the correlation product moment formula with the help of SPSS version 16. The results of this study indicate that there was a significant influence on the cooperative learning model of TGT type in the interest learning Arabic language in MTs. Negeri Banggai Kepulauan, Central Sulawesi. It was proven by the score of rcount 0,771 while rtable 0,404. It meant that the score of rcount was greater than the score of rtable with a significant level of 5%. Based on the decision making criteria and testing, the cooperative learning model of TGT type in the interest learning Arabic language in VII grade students was categorized into strong category of influence.